Multi-party verifiable arbitrated quantum signature scheme with information hiding function - Gao, Qin; Lu, Dianjun; Wen, Dongqin; Renqian, Suonan; Wei, Xingjia (Laser physics letters, 2025)
With the progress of science and technology, more and more researchers have begun to pay attention to quantum digital signature schemes. Arbitrated quantum signatures have attracted much attention due to their many advantages. This paper presents a multi-verifiable arbitrated quantum signature scheme with information hiding function. In this scheme, the original information and the shared key are hidden in the Bell state, so that any attacker cannot obtain the original information through quantum measurement. In this scheme, multi-verifiers connect end to end to form a ring, and the feasibility of the scheme can be verified if and only if all verifiers participate. Ring verifiers select one of them as the representative. The representative uses the one-way hash function for authentication and indicates the identity to the arbitrator. Therefore the arbitrator does not need to verify the identities of all the verifiers and improves the authentication efficiency. The security analysis shows that the scheme is undeniability, unforgeability and can resistant to intercept-resend attacks, combined attacks and cheating attacks.